Repercussions and Challenges to the Production of the Psychology: Organizations and Work Journal - Roberto Moraes Cruz; Jairo Eduardo Borges-Andrade; Daniela Bahia Moscon; Marcos Ricardo Datti Micheletto; Marina Greghi Sticca; Mary Sandra Carlotto; Germano Gabriel Lima Esteves; Paola Barros-Delben (Revista Psicologia)
Repercussões e Desafios à Produção da Revista Psicologia: Organizações e Trabalho Repercussions and Challenges to the Production of the Psychology: Organizations and Work Journal Repercusiones y Desafíos a la Producción de la Revista Psicología: Organizaciones y Trabajo